2022
DOI: 10.1051/0004-6361/202243993
|View full text |Cite
|
Sign up to set email alerts
|

KMHK 1762: Another star cluster in the Large Magellanic Cloud age gap

Abstract: Context. The star cluster (SC) age distribution of the Large Magellanic Cloud (LMC) exhibits a gap from ∼4 to 10 Gyr ago, with an almost total absence of SCs. Within this age gap, only two confirmed SCs have been identified hitherto. Nonetheless, the star field counterpart does not show the same characteristics, making the LMC a peculiar galaxy where the star formation history and cluster formation history appear to differ significantly. Aims. We re-analysed the colour-magnitude diagram (CMD) of the KMHK 1762 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…However, recent investigations based on relatively deep photometry have shown that several faint candidate star clusters in regions of the LMC not investigated before can have ages falling in the age-gap (Gatto et al 2020). In addition, a reanalysis of the CMDs of the star clusters KMHK 1592 and KMHK 1762 based on deep photometry showed that both star clusters fall inside the age-gap, at odds with previous age estimates based on too-shallow photometry (Gatto et al 2022;Piatti 2022). These findings seem to suggest that the age-gap is not a real physical feature, but the result of an observational bias, originated by the combination of too-shallow photometry carried out in the literature, the lack of a proper decontamination of field stars and an incomplete investigation of the LMC outskirts, where the lower stellar density of the field permits the detection of even faint and sparse star clusters.…”
Section: Census and Properties Of Star Clusters In The Magellanic Cloudsmentioning
confidence: 82%
“…However, recent investigations based on relatively deep photometry have shown that several faint candidate star clusters in regions of the LMC not investigated before can have ages falling in the age-gap (Gatto et al 2020). In addition, a reanalysis of the CMDs of the star clusters KMHK 1592 and KMHK 1762 based on deep photometry showed that both star clusters fall inside the age-gap, at odds with previous age estimates based on too-shallow photometry (Gatto et al 2022;Piatti 2022). These findings seem to suggest that the age-gap is not a real physical feature, but the result of an observational bias, originated by the combination of too-shallow photometry carried out in the literature, the lack of a proper decontamination of field stars and an incomplete investigation of the LMC outskirts, where the lower stellar density of the field permits the detection of even faint and sparse star clusters.…”
Section: Census and Properties Of Star Clusters In The Magellanic Cloudsmentioning
confidence: 82%